2023
DOI: 10.1093/jee/toac193
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of Two Chitin Synthases in the Black Cutworm, Agrotis ipsilon (Hufnagel) (Lepidoptera: Noctuidae)

Abstract: The black cutworm, Agrotis ipsilon (Hufnagel), a seasonal migrant and a prolific generalist, can feed on nearly all vegetables and grain crops, causing considerable economic impacts on a global scale. Given its cryptic nature, A. ipsilon management has been extremely challenging. Chitin synthase (CHS), a key enzyme involved in chitin biosynthetic pathway and crucially important for the growth and development of insects, is the molecular target of chitin synthesis inhibitors, a group of broad-spectrum insectici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…60 Silencing of chitin synthase and chitinase genes in A. ipsilon was successfully conducted by injection of dsRNA, and knockdown of these genes induced high larval mortality. 61,62 We performed RNAi analysis to evaluate the role of AiGSTu1 in the detoxification of CAP. The results showed that dsAiGSTu1 injection significantly reduced the expression level of AiGSTu1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Silencing of chitin synthase and chitinase genes in A. ipsilon was successfully conducted by injection of dsRNA, and knockdown of these genes induced high larval mortality. 61,62 We performed RNAi analysis to evaluate the role of AiGSTu1 in the detoxification of CAP. The results showed that dsAiGSTu1 injection significantly reduced the expression level of AiGSTu1.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi is a post‐transcriptional gene silencing process and a powerful tool for studying the functions of genes by suppressing gene expression 60 . Silencing of chitin synthase and chitinase genes in A. ipsilon was successfully conducted by injection of dsRNA, and knockdown of these genes induced high larval mortality 61,62 . We performed RNAi analysis to evaluate the role of AiGSTu1 in the detoxification of CAP.…”
Section: Discussionmentioning
confidence: 99%
“…Chitin is the main component of the cuticle and peritrophic membranes of insects [ 10 , 11 , 12 , 13 , 14 ], and the disruption of the chitin metabolism has a lethal effect on insects [ 15 , 16 , 17 , 18 , 19 ]. For example, the silencing a chitin synthase of Spodoptera frugiperda (Lepidoptera: Noctuidae) that is highly expressed in the cuticle caused a high rate of larval mortality and pupal malformation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%